Implementasi Tes Mata Pelajaran Ekonomi Berbasis HOTS - Tri Kurniawati; Abel Tasman (Universitas Negeri Padang, 2021)
This study aimed to explore the use of HOTS-based tests by teachers in West Sumatra. This research was conducted in Bukittinggi City, Agam Regency and Pesisir Selatan Regency. This research was conducted with a descriptive approach. The results of this study indicate that there is no use of HOTS-based tests on daily tests, midterm and semester exams are still low. This requires training and mentoring for teachers to train their skills in developing HOTS economic questions.Keywords : tests, HOTS, economic